Development of Anti Acne Cream (w/o/w Multiple Emulsion) Containing Green Tea Leaf Waste - Naniek Widyaningrum (Universitas Sultan Agung Semarang, 2018)
Background: To date, green tea leaf waste is not well utilized, the waste is remain considered as a waste. Previous studies found that green tea leaf waste still have a fairly high EGCG content. EGCG has benefits as an antibacterial. Utilization of green tea leaf waste started from formulation until the diversification of multiple emulsion w/o/w products has not been reported.